Bipartite 2‐Factorizations of Complete Multipartite Graphs. Issue 4 (7th May 2014) - Bryant, Darryn; Danziger, Peter; Pettersson, William
Abstract It is shown that if K is any regular complete multipartite graph of even degree, and F is any bipartite 2‐factor of K, then there exists a factorization of K into F; except that there is no factorization of K6, 6 into F when F is the union of two disjoint 6‐cycles.